METHODS OF CONTROL OF VERTICAL JUMP DISTANCE IN SPORTS - Bilenko A.G. ,; Losin B.E. ,; Ivanova G.P. ,; Baryaev A.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the degree of reliability and appropriateness of using methods for determining the jump height of athletes based on theoretical analysis and generalization of practical experience. Methods and structure of the study. A theoretical review of the available literature was conducted, as well as pedagogical testing: measuring the vertical jump height of forty athletes specializing in various team sports. In addition, dynamometric measurements of jump characteristics were carried out using a computerized data processing system synchronized with high-speed video recording. Results and conclusions. The variety of existing methods for determining jump height indicates their applicability in various sports disciplines, since each of them meets the needs of a specific sport. However, comparing the results obtained in different sports areas seems unjustified without unifying the measurement methods. The difference in accuracy due to the use of different methods can reach 30-40%. Due to the lack of uniform standards for determining jump height, in practice jumping ability is often assessed as a specific skill characteristic of a certain sports specialization, and not as a general physical characteristic. The most accurate and objective way to determine the true jump height is dynamometry, which allows excluding the influence of specific skills and abilities inherent in specific sports. Using only age, gender and qualification standards is insufficient due to the significant variability of this indicator within homogeneous groups of athletes. When monitoring and assessing jumping ability, it is advisable to take into account the anthropometric data of athletes, in particular their height, as well as their playing role, as is customary in some team sports.